Drainage basin and topographic analysis of a tropical landscape: Insights into surface and tectonic processes in northern Borneo - Manoj Joseph Mathew, David Menier, Numair Siddiqui, Mu Ramkumar,, . (2016)
We investigated the recent landscape development of Borneo through geomorphic analysis of two large drainage basins (Rajang and Baram basins).